Fast software encryption : 23rd International Workshop, FSE 2016, Bochum, Germany, March 20-23, 2016. Revised selected papers /: 23rd International Workshop, FSE 2016, Bochum, Germany, March 20-23, 2016. Revised selected papers. (2016) - Unknown
No abstract available